Effect of drought stress on dieback disease development under Lasiodiplodia theobromae infection in cocoa clone 'MCC 02' - Asman Asman; Toru Iwanami; Ade Rosmana (Beverage Plant Research)
Cocoa is spread over tropical countries, being extensively cultivated by mostly smallholders and processed by industries as the raw material of chocolate. Pathogens and drought are one of the biotic and abiotic factors limiting the productivity of cocoa. The main objective of this study was to evaluate the pathogenicity of Lasiodiplodia theobromae in drought-stressed and well-watered cocoa clone MCC 02. MCC 02, a popular cocoa clone in Sulawesi (Indonesia), was evaluated in the greenhouse for infection of L. theobromae under water-stressed and well-watered conditions. Dieback, leaf chlorotic and necrotic, scion survival, and vascular streaking were determined. The results indicated that the treated cocoa seedlings exposed to water stress corresponding to 25% field capacity during both inoculation of the pathogen simultaneously with the initiation of water stress or seven days after water stress commenced were more susceptible to L. theobromae than well-watered ones. However, this effect was mainly relevant when the pathogen was inoculated through a wound on the stem. Moreover, the severity of the disease on inoculation of L. theobromae simultaneously with the initiation of water stress was higher than that of the disease on inoculation seven days after water stress commenced but not significantly different. This study demonstrates the potential threat of drought stress to cocoa plants under the infestation of L. theobromae and emphasizes the significant effect of water stress in interaction with L. theobromae that should be considered in plant management, especially under the climate change scenario in Sulawesi, in which the drought will increase and last longer.